BIODIESEL PROCESS PRODUCTION FROM WASTE COOKING OIL USING MICROWAVES AND HIGH VOLTAGE - Trisnaliani, Lety; Moulita, RA Nurul (KINETIKA, 2017)
Increasing fuel demand has an impact for decreasing fossil energy reserves. One of the government ways to solve this problem is by increasing the production of biomass fuels, for example biodiesel. Biodiesel can be produced from waste cooking oil through the transesterification stage that reacts oil molecules with alcohol and catalyst to produce methyl esters. Heating method that can be used is microwaves method. This method utilizes wave emission which is absorbed by the sample to make sample’s temperature being higher than surface’s temperature of the reactor’s wall. In the process of making biodiesel, there are several factors that affected heating process. There are ratio of waste cooking oil and methanol, an amount of catalyst, reaction temperature, voltage, and distance of electrodes. The effect of that factors can be seen from the result of the biodiesel’s rendement. From this research, we had ratio 5:1 of waste cooking oil and methanol got 85,. % rendement, 2% of catalyst got 87.12% rendement, 60oC reaction temperature got 88.88% rendement, 10 kV got 89.12% rendement, and 1 cm of electrode’s distance got 86.34% rendement. This result suggests that a biodiesel production prototype with microwaves and high voltage utilization can produce a high percentage of biodiesel rendement